Heart transplantation from an extended criteria donation after circulatory death donor. (11th February 2022) - Vokshi, Ismail; Large, Stephen; Berman, Marius; Tsui, Steven
Abstract: Transplantation of donation after circulatory death (DCD) donor hearts is gaining acceptance. However, DCD heart selection has been understandably cautious. We report a case of reconditioning a DCD heart using thoraco-abdominal normothermic regional perfusion in a 46-year-old donor who suffered irreversible brain injury following emergency type-A aortic dissection repair. The DCD heart was procured with cold preservation and directly transplanted into a 63-year-old male who was bridged to transplant with extracorporeal life support. The recipient required a brief period of mechanical circulatory support post-transplant but made a good recovery. To our knowledge, this is the first report of successful heart transplantation from such an extended criteria DCD donor. Abstract : The 46-year-old male donor underwent emergency acute type-A aortic dissection repair 4 days prior involving re-suspension of the aortic valve and an interposition graft to the proximal arch (Table 1a).